2019
DOI: 10.1002/er.4846
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of repowering optimization for an existing photovoltaic‐pumped hydro storage hybrid system: A case study in Sichuan, China

Abstract: Summary For a remote area or an isolated island, where the grid has not extended, a standalone hybrid energy system can provide cheap and adequate power for local users. However, with the development of society, the load demand will increase and the original system cannot completely meet the load demand. This situation occurs in Xiaojin, Sichuan, China. The existing photovoltaic‐pumped hydro storage (PV‐PHS) hybrid system in this area as the original system cannot completely meet the load requirements at prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The SAPSO is a heuristic algorithm combining particle swarm optimization (PSO) method (Xu et al, 2019b(Xu et al, , 2020b and simulated annealing (SA) method (Javidrad and Nazari, 2017). PSO mainly relies on the information between particles to update their position and velocity in the optimization process.…”
Section: Simulated Annealing Based Particle Swarm Optimization Methodsmentioning
confidence: 99%
“…The SAPSO is a heuristic algorithm combining particle swarm optimization (PSO) method (Xu et al, 2019b(Xu et al, , 2020b and simulated annealing (SA) method (Javidrad and Nazari, 2017). PSO mainly relies on the information between particles to update their position and velocity in the optimization process.…”
Section: Simulated Annealing Based Particle Swarm Optimization Methodsmentioning
confidence: 99%
“…Overall, the optimal sizing of PSP in MRES should take more factors into consideration, including the high investment cost of PSP unit. The relevant research can be found in [44], [45] and it will not be studied in this paper.…”
Section: E Sensitivity Analysis Of Mres Configuration Under Different...mentioning
confidence: 99%
“…To produce solar radiation scenarios, the normal distribution function can be employed. The available power generated by the PV power station in each period and scenario can be formulated as [35]:…”
Section: Pv Power Stationmentioning
confidence: 99%
“…This work investigates the operational problem of the proposed HERS; therefore, the detailed parameters of the PV power station and hydrogen production system are given in Table 1 [35] and Table 2 [37], respectively. Notably, the size of the electrolyzer is greater than that of the fuel cell, as the electrolyzer needs to produce more hydrogen to meet the demand of the HFCVs and fuel cell.…”
Section: Datamentioning
confidence: 99%